Factors associated with unmet need of family planning in Bihar, India: a spatial and multilevel analysis - Pal, Anita; Yadav, Jeetendra; ., Sunita; Singh, Kh. Jitenkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Many women in low and middle-income countries would like to limit or delay their pregnancy, but they do not enough access to consistent use of modern contraceptive methods. The concept of unmet need for family planning is focus to reproductive health policies, as it endures serious implications for the women, the child, family and the whole society. The aims of the study are to assess the spatial dimensions of extent of unmet need for family planning and also identify association between individual, household, community and district level covariates with the level of unmet need for family planning among married women of reproductive age group in Bihar, India. Methods: The study uses data from fourth round of the National Family Health Survey (NFHS-4). To meet the objective the analysis included descriptive, spatial visualization, spatial autocorrelation and multilevel logistic model. In the first step of analysis the multivariate analysis was used to know the levels of unmet need for family planning by selected background characteristics. Results: This study indicating that nearly one in five or more women experiences unmet need for family planning suggests that the problem remains of considerable magnitude and that action is needed to fill the gap in contraceptive use, which is currently estimated at a lowest 24 percent. Apart from providing a current estimate of unmet need, our study identified a number of relevant socioeconomic and demographic factors likely to shape the probability that a women experiences unmet need. It is observed across individual level, community/psu level and district level. Conclusions: Considering this fact, family planning program in Bihar should also focus on eliminating misconceptions and fear about contraception through proper counselling of couples and information, education and communication activities in the community and try to improve the quality of advice and care services related to family planning.